2005
DOI: 10.1038/sj.cdd.4401569
|View full text |Cite
|
Sign up to set email alerts
|

Zonal necrosis prevented by transduction of the artificial anti-death FNK protein

Abstract: Protection of cells from necrosis would be important for many medical applications. Here, we show protein transduction domain (PTD)-FNK therapeutics based on protein transduction to prevent necrosis and acute hepatic injury with zonal death induced by carbon tetrachloride (CCl 4 ). PTD-FNK is a fusion protein comprising the HIV/Tat PTD and FNK, a gain-offunction mutant of anti-apoptotic Bcl-x L . PTD-FNK protected hepatoma HepG2 from necrotic death induced by CCl 4 , and additionally, increased the apoptotic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 59 publications
3
30
0
Order By: Relevance
“…PTD-FNK affected the movement of calcium ions, leading to the protection of primary neurons against glutamate toxicity, directly or indirectly (Asoh et al, 2002). We also demonstrated that PTD-FNK retains the mitochondrial membrane potential and the intracellular ATP level to protect hepatoma cells from necrosis induced by carbon tetrachloride (Asoh et al, 2005). In the ischemia/reperfusion injury model using Langendorff's heart, it is likely that PTD-FNK contributes to calcium homeostasis and/or mitochondrial activity to inhibit myocardial cell death, regardless of the form of cell death.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…PTD-FNK affected the movement of calcium ions, leading to the protection of primary neurons against glutamate toxicity, directly or indirectly (Asoh et al, 2002). We also demonstrated that PTD-FNK retains the mitochondrial membrane potential and the intracellular ATP level to protect hepatoma cells from necrosis induced by carbon tetrachloride (Asoh et al, 2005). In the ischemia/reperfusion injury model using Langendorff's heart, it is likely that PTD-FNK contributes to calcium homeostasis and/or mitochondrial activity to inhibit myocardial cell death, regardless of the form of cell death.…”
Section: Discussionmentioning
confidence: 89%
“…PTD-FNK was shown to suppress hepatic necrosis caused by carbon tetrachloride in vitro and in vivo as well as apoptosis (Asoh et al, 2005). Importantly, PTD-FNK is effective for post-treatment (Asoh et al, 2005). Moreover, PTD-FNK protected neurons from delayed neuronal cell death caused by ischemic brain injury, when intraperitoneally injected into animal models (Asoh et al, 2002).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…7,8 We first constructed a powerful artificial antiapoptotic protein, FNK (originally designated Bcl-xFNK by Asoh et al 9 ), which has three amino-acid substitutions, Tyr-22 to Phe(F), Gln-26 to Asn(N) and Arg-165 to Lys(K), to strengthen the cytoprotective activity of Bcl-x L . We then demonstrated that fusion of FNK with TAT enabled FNK to penetrate highly negatively charged chondrocytes 9,10 and the blood --brain barrier, 11 and that TAT-FNK showed an antiapoptotic effect in a model of brain and hepatic ischemia. 11,12 When injected intraperitoneally into guinea pigs in vivo, we observed that TAT-FNK was distributed widely in the cochlea and that it reduced the expression of cleaved poly-(ADP-ribose)-polymerase (PARP), auditory brainstem response (ABR) threshold shifts, and HC loss induced by a combination of ethacrynic acid (EA) and kanamycin sulfate (KM), in vivo.…”
Section: Introductionmentioning
confidence: 96%
“…Asoh and co-workers showed that the PTD-fused FNK protein, constructed from Bcl-X L by the site-directed mutagenesis of three amino acids improves cytoprotective activity Yamada, Y., et al 10 (Asoh et al, 2000), protected a certain type of cells from both necrotic and apoptotic cell death (Asoh et al, 2002, Asoh et al, 2005 (Fig. 1 C).…”
mentioning
confidence: 99%